Pengaruh Cara Penyembelihan dan Lama Penyimpanan Terhadap Kualitas Daging Ayam Broiler - Anis Dliyaul Haq; Irfan Irfan; Yanti Meldasari Lubis (Agricultural Faculty, 2020)
Slaughtering is a method used to obtain food from farmed animals. Chicken slaughter is one of important factors affevting the halal and nutritional quality of meat. Chicken meat slaughtered is done according to islamic sharia and not according to Islamic sharia. Slaughtering is carried out according to islamic or halal sharia according LPPOM-MUI (2008). The storage time for food is a period of time that is safe and suitable for consumption in food and can be used by consumers according to their needs and can maintain the state of the food that is packed. Determine the quality of chicken meat whether or not accepted by consumers affect the physical, chemical and biological quality. The study aims to determine the effect of slaughtering methoda (according to Islamic sharia and not according to Islamic sharia) and duration of storage on the quality of chicken meat. This research uses factorial randomized block design (RBD) consisting of 2 factors. The first factor is the method of slaughtering, namely slaughtering by Islamic sharia and slaughtering not by Islamic sharia (neck slaughter broken). Slaughtering by Islamic sharia is chicken slaughtering in RPA that is halal certified, while slaughtering is not by Islamic sharia is chicken slaughtered in RPA that is certified not halal. The second factor is storage time, which is 0 hours (control), 3 hours, 6 hours and 9 hours. The result of this study showed that slaughter had a very significantly affected (P 0,01) on skin color. The treatmment duration significantly affected (P 0,05) on water content and suppleness. Research shows that the quality of chicken meat slaughtered according to Islamic sharia (P1) is better than meat slaughtered not according to Islamic sharia, especially in terms of; as higher skin color. As storage time increases, the water content